The Kuroshio frontier : empire and environment in the making of Japan's Pacific - Rüegg, Jonas (Cambridge oceanic histories., 2026)
This big-picture narrative of modern Japan embeds the archipelago's history in its maritime context. Foregrounding the Kuroshio Current in the Pacific, Jonas Rüegg demonstrates how currents, winds, and animals created a dynamic context to economic, intellectual, and geopolitical reinventions of Japan over the past four centuries. He draws up a novel geography of conflicts and competitions in the making of 'modern' Japan, one that underlines little known actors, sites, and events which have previously been treated as peripheral. This book offers a framework that transcends conventional spatial and temporal categorizations of early modern and modern, shogunal and imperial, insular and global. Guiding the reader from seventeenth-century Pacific explorations to the "opening" of Japan by whalers, coolies, and castaways, and on to the competition over remote islands, Rüegg offers a greater perspective on the role of oceans in the Anthropocene. This title is also available as Open Access on Cambridge Core.